Hull design & stability analysis of GRP Bedar / Mohamad Noor Asnawi Noor Azhari - Noor Azhari, Mohamad Noor Asnawi (2022)
Technology is developing every day. This results in a growing forgetfulness about traditional items. This also includes Bedar, a prized piece of Terengganu tradition. In addition, there are other issues including rising expenses, the endangerment of chengal wood, and a shortage of expertise. The project's main goal is to update the hull design so that it will be simpler for future generations to recreate the Bedar Boat. The stability of the hull must also be reanalysed when the hull design is changed. this includes weight estimation, stability analysis for transverse and longitudinal directions, general arrangement drawings, and hydrostatic curves. To ensure the success of this project, the lines plan will first be created using the chosen hull design, in this case, a round-bottom hull. Following that, a 3D model will be created using PolyCAD software based on the lines plan. All of the analysis will be carried out with ease once the model is complete using PolyCAD, Rhino and other software. After finishing this project, we will achieve a simpler method for building Bedar boats utilising modern techniques and analyses. The bedar boat will once more become well-known and acknowledged and will not be lost to the ravages of time.